The Effect of Arm Resistors Training on the Accuracy of Shooting with Light Weapons - Raheem Mashaf, Rasool; Abdulrahman Werytha, Natiq (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the effect of strength training on the accuracy of shooting with light weapons and to identify the preference of the impact of strength training on the accuracy of shooting with light weapons for employees of the Personal Protection Police. Experimental and control, and there are significant statistical differences between the experimental and control groups in the results of the dimensional tests for the level of accuracy of shooting with light weapons, so the experimental research method is designed by designing the experimental and control groups E, on a sample of (20) member chosen by intentional (71.428%) of the Internal Security Forces participating in the training session development for the year (2019-2020) in the protection of Baghdad Directorate figures the tasks and duties section, they were randomly divided into two groups of equal number, experimental and controlling for each group (10) associates, and resistance training for the arms was applied, which are modern methods that were codified to suit the effectiveness of the sample and their application and applied for a period of (8) training weeks at a rate of (3) per week, and was measured By testing the light weapons of the handgun and the rifle from the standing and brook positions approved in their cycle for shooting accuracy and the results handling system (SPSS-V26) to be the conclusions and applications that the application of resistance training helps members of the protection force characters improve the accuracy of their shooting with light weapons in the two weapons (item The position of the pistol) is from the positions (standing and brook), and their superiority over the improvement in the level of this accuracy with shooting with light weapons among their peers who are trained without it, and it is necessary for training means to suit the type of strength training in light weapons and the privacy of members of the personal protection force, and it is necessary to codify the load training for strength training according to the capabilities of the associates themselves, by adopting experimentation when training them.